(3QSGdI Cf GdeUWaj Udi Gddg Ydjg hSde dGjNdh efg ecGfs - (3eMeO Ydj Hf YdGf GdUOjbi GdTGaYjs; (3Ydj fhQ GdOjfs
(3ChdgG (B:s
(3GdMeO ddg GdbGOQ Ydi cd eecf hHYO ajbhd abjQ QMeI ehdGg EP JhTM Hg GdChGf jOYi EJMGa Cgd GdESdGe hGdEjeGf HCf GdeUWai Udi Gddg Ydjg hSde dGjNdh Yfg ecGf hdG ReGf dNUJ ajg JYQja Cgd GdESdGe s
(3BNQgG (B:s
(3ced LYd ai LSOg GdTQja eYfi ef eYGfi GdedGFcI acGf jNGdW Gdedc LHQGjd hGSQGFjd GdPjf geG QFjSG ddedGFcI dCf ESQGajd JQOO dNOeJg KdGK Sfjf bHd SjOfG LHQjd Udi Gddg Ydjg hSde gPG BNQ eGdNUJg ef eDdag s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B15s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs